The Effect of Hypoxic Mesenchymal Stem Cells on the expression of Transforming Growth Factors in Wistar Rats Excision Wound Model - Istiqomah, Dyah Ayu Fitri; Djannah, Durrotul; Mulyani, Sri Priyantini (International Journal of Cell and Biomedical Science, 2022)
Background: Hypoxic Mesenchymal stem cell (MSC) therapy may accelerate the wound healing process through a paracrine mechanism by increasing the expression of transforming growth factor-β (TGF-β). Objective: This study aims to investigate the effect of hypoxic MSC on TGF-β gene expression in excision wound models. Methods: This is an experimental study with a post-test-only control group design. Sixty male Wistar rats were divided into 4 groups consisting of 5 each to represent group I (sham/normal control), group II (excision wound model), group III (excision wound model and normoxic MSC injection), group IV (excision wound model and hypoxic MSC injection) for observation of TGF-β gene expression on days 3, 6 and 9. Both MSC (3x106 cells) were injected subcutaneously after wound excision at five locations 0,5 cm from the wound edge. TGF-β gene expression was examined by qRT-PCR. Results: The highest average TGF-β gene expression on the three observation days were shown by group II. TGF-β gene expression in groups III and IV was lower than in group II, while groups III and IV were relatively similar. In the normal wound healing process, TGF-β is highly expressed, and both MSC injection reduces TGF-β gene expression. Conclusion: Hypoxic MSC injection accelerated the proliferative phase of the excisional wound healing process, but the acceleration effect was equivalent to that shown by Normoxic MSC.